Nitrogênio, carbono e agregação do solo sob sistemas de uso no território do Caparaó-ES - Ribeiro, Jadson Jordão (2015)
Soil conservation techniques, such as vegetation cover, aim to maintain or increase soil organic matter to keep in balance the chemical, physical and biological soil. Constant supply system of organic matter such as agro-ecological systems, appears as a v